Impact of organic binders on the carminic-colorants stability studied by: ATR-FTIR, VIS and colorimetry. (February 2021) - Haberová, Katarína; Jančovičová, Viera; Veselá, Dominika; Machatová, Zuzana; Oravec, Michal
Abstract: Carminic acid is the main coloring component of cochineal (a red organic dye extracted from female bodies of Dactylopius coccus ). The utilization of the dye in specific painting techniques is determined by the addition of suitable binders, which influence the light and thermal stability of the color layer. In this work, the influence of some plant-based binders (maize starch, gum arabic) and some binders of animal origin (egg albumen, gelatin) on light and thermal stability of model systems with carminic acid was studied. As colorants, two available commercial colorants were used – the carminic acid and Carmine Naccarat, and two colorants prepared in the laboratory – the cochineal carmine and cochineal. The color layers were subjected to accelerated light and thermal aging. For characterization of the color layers and changes of their properties during accelerated aging the spectral methods (ATR-FTIR, VIS) and colorimetry were used. Comparison of the influence of the binders on light stability of the color layers showed the layers with albumen were the least stable, whereas the layers with gum arabic were the most stable. No significant color changes were detected during thermal aging . Highlights: 16 model color layers based on red carmine colorants and binders (starch, gelatin, albumen, maize). Influence of painting formulation on color coordinates and VIS spectra. Two type of accelerated aging: light aging in Q-sun and thermal aging at 65 °C. Changes of total color difference and VIS spectra of color layers upon aging. The high photostability of layers with gum arabic in comparison with egg albumen.